Renal transplantation in patients with Alport syndrome: patient selection, outcomes, and donor evaluation - Kashtan CE (International Journal of Nephrology and Renovascular Disease, 2018)
Clifford E Kashtan Division of Nephrology, Department of Pediatrics, University of Minnesota Medical School, Minneapolis, MN 55454, USA Abstract: Alport syndrome is an inherited disorder of basement membrane collagen IV that frequently results in end-stage renal disease. Patients with Alport syndrome who undergo renal transplantation have generally excellent outcomes. Posttransplant antiglomerular basement membrane nephritis is a rare complication of renal transplantation for Alport syndrome. Because Alport syndrome is a genetic disorder, potential related donors must be carefully evaluated in order to minimize harm. Keywords: Alport syndrome, kidney transplantation, collagen IV, posttransplant anti-GBM nephritis